THE IMPLEMENTATION OF KWL STRATEGY TO IMPROVE STUDENT’S READING COMPREHENSION - Fatin Nabila; I Gde Putu Agus Pramerta; Anak Agung Putri Maharani (Academic Journal on English Studies (AJOES), 2022)
The study aims to find out the reading comprehension of the eighth-grade students of SMP Dharma Praja Denpasar after being treated with KWL strategy with picture. This research made use a Classroom Action Research which took two cycles: two sessions for each cycle. Pre-test, post-test, and questionnaire were administered for the data collection. The findings revealed that there was a significant improvement of the students' achievement. It was respectively improving from the pre-test 65.33 and post-test 78.23. From the questionnaire that was administered in the last cycle, the students gained positive response in terms of their changing learning behavior towards the application of KWL strategy. Based on the findings, the reading comprehension of the subjects can be improved through KWL strategy with picture.